Chemical composition of two mineralogically contrasting Arctic bivalves' shells and their relationships to environmental variables. Issue 2 (30th January 2017) - Iglikowska, A.; Bełdowski, J.; Chełchowski, M.; Chierici, M.; Kędra, M.; Przytarska, J.; Sowa, A.; Kukliński, P.
Abstract: The main goal of this study was to determine the concentrations of trace elements in the mineralogically contrasting shells of two Arctic bivalves: Chlamys islandica and Ciliatocardium ciliatum . Aragonite shells seem to be more susceptible to the binding of metal ions, which is most likely a result of their crystal lattice structure. We suggest that less biologically controlled aragonite mineralization tends to incorporate more metal impurities into the crystal lattice in waters with a lower pH, where metal ions are more available. Higher concentrations of impurities may further increase the lattice distortion causing lower crystal lattice stability and higher susceptibility to dissolution. Calcitic shells seem to be less prone to bind metal ions than aragonite shells most likely because under strict biological control, the uptake of ions from ambient seawater is more selective; thus, the final crystal lattice is less contaminated by other metals and is more resistant to dissolution. Highlights: The CaCO3 polymorph plays a key role in the uptake and retention of trace elements. Lower pH aragonitic shells seem to be less prone to bind metal ions. Under strict physiological control the ions uptake into calcite is highly selective. Similar trace element concentrations in all size classes of studied species.